Biomarkers of dyslipidemia in patients with diabetic foot - Vujčić, Sanja; Stefanović, Tatjana; Zeljković, Aleksandra; Mihajlović, Marija; Vekić, Jelena (Archives of Pharmacy, 2022)
Diabetic foot (DF) is one of the most severe complications of diabetes that significantly reduces the quality of life and survival of patients. Besides firmly established risk factors, novel data indicate that alterations in lipid metabolism might also be implicated in the development and progression of DF. Diabetic dyslipidemia is characterized by the atherogenic triad, consisting of increased triglycerides (TG), decreased high-density lipoprotein cholesterol (HDL-C) levels and the presence of small, dense low-density lipoprotein (LDL) particles. Accumulating evidence suggests that profound hypertriglyceridemia and HDL-C reduction are common findings in patients with diabetic neuropathy and significantly contribute to an increased risk for DF, amputation and mortality. Small, dense LDL particles play an important role in the development of cardiovascular complications of diabetes, but their clinical importance in patients with DF remains to be established. In this paper, we will discuss the significance of standard and novel lipid biomarker determination in the assessment of the risk for the development and progression of DF.
Keywords: lipid profile; small dense LDL; HDL functionality; diabetes